DETERMINAN UNTUK MENILAI KINERJA KEUANGAN - Ayom Handayani; Ismunawan Ismunawan (Juremi: Jurnal Riset Ekonomi, 2023)
This study aims to analyze liquidity, profitability, solvency, activity and firm size on the financial performance of chemical manufacturing companies in the Indonesia Stock Exchange for the 2017-2021 period. The research approach used in this research is quantitative. The population of this research is all manufacturing companies in the chemical sub-sector on the IDX. Sampling in this study using purposive sampling method with a total sample of 9 companies and 5 periods of financial statements. Analysis of liquidity indicators Current Ratio (CR). Analysis of profitability indicators Return on Equity (ROE). The solvency analysis of the indicator is Debt to Equity Ratio (DER). Analysis of activity indicators Inventory Turnover (IT). The indicator company size is Ln total assets. Financial performance is assessed with the Return on Assets indicator. The analysis technique used was descriptive statistics, classical assumption test (multicollinearity test and autocorrelation test), t test, f test, coefficient of determination test and multiple linear regression analysis. The results of this study indicate that Liquidity (CR) has a significant effect on financial performance, Profitability (ROE) has a significant effect on financial performance, Solvency (DER) has a significant effect on financial performance, Activity (IT) has no significant effect on financial performance. (LN) has a significant effect on improving financial performance. Together, Liquidity (CR), Profitability (ROE), Solvency (DER), Activity (IT) and Firm Size have a significant effect on financial performance